Suppressing Electron Back‐Donation for a Highly CO‐tolerant Fuel Cell Anode Catalyst via Cobalt Modulation - Yang, Yu; Gao, Fei‐Yue; Zhang, Xiao‐Long; Qin, Shuai; Zheng, Li‐Rong; Wang, Ye‐Hua; Liao, Jie; Yang, Qing; Gao, Min‐Rui (Angewandte Chemie International Edition, 2022)
Platinum on carbon (Pt/C) catalyst is commercially adopted in fuel cells but it undergoes formidable active‐site poisoning by carbon monoxide (CO). In particular, given the sluggish kinetics of hydrogen oxidation reaction (HOR) in anion‐exchange membrane fuel cell (AEMFC), the issues of Pt poisoning and slow rate would combine mutually, notably worsening the device performances. Here we overcome these challenges through incorporating cobalt (Co) into molybdenum‐nickel alloy (MoNi4), termed Co‐MoNi4, which not only shows superior HOR activity over the Pt/C catalyst in alkali, but more intriguingly exhibits excellent CO tolerance with only small activity decay after 10 000 cycles in the presence of 500 parts per million (ppm) CO. When feeding with CO (250 ppm)/H2, the AEMFC assembled by this catalyst yields a peak power density of 394 mW cm−2, far exceeding the Pt/C catalyst. Experimental and computational studies reveal that weakened CO chemisorption originates from the electron‐deficient Ni sites after Co incorporation that suppresses d→CO 2π* back‐donation. Incorporating Co into MoNi4 nanocatalyst can suppress the d→CO 2π* back donation, leading to excellent CO tolerance. When feeding with CO (250 ppm)/H2, the fuel cell assembled by this catalyst yields a peak power density of 394 mW cm−2, exceeding that of 209 mW cm−2 for the Pt/C catalyst.